Implementation problems in integrated rural development : a case study of the Rapti Integrated Rural Development Project, Nepal - Aryal, Sushil Babu; Tips, Walter E. J.; Weber, Karl E.; Oudheusden, Dirk L. van; The Canadian International Development Agency-Broad Based Development Program (CIDA-BBDP) (Bangkok : Asian Institute of Technology, 1986)
This study identifies the implementation problems in the organizational structure, in the inter-organizational coordination, in the administrative and management system and in the people's participation of the Rapti Integrated Rural Development Project. The study reveals that there are problems with the management procedures rather than with the organizational structure of the project . The centre has not delegated adequate authority to the local level offices for project implementation even though a new Decentralization Act has been adopted one year ago . The implementing agencies are not clear about their role, authority and responsibility and hence in most cases the implementation issues are referred back to Kathmandu for decision making. Lack of effective coordination exists both in vertical and horizontal operations which results in delays in implementation . District level officials are more responsible to their regular departmental programmes rather than to the !RD programmes. Delays in releasing funds have adversely affected the timely completion of the project. Due to the remoteness and lack of incentives and motivation, there is a lack of technical manpower in the district. and project . level offices . People's participation is only developed as voluntary labour contributions . The people are not involved in the project formulation, implementation, evaluation or follow up.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1986
Keywords: Rural development -- Nepal